A Study on the Influence of Thai Cultural Factors on Attitudes and Perceptions of Adhd - Mason, Eric; Varma, Parvathy (Scholar: Human Sciences, 2021)
The current research examined Thai cultural factors, such as religiosity, stigmatization of mental disorders, holistic thinking, and health locus of control towards attitudes and perceptions of ADHD, moderated by prior exposure to ADHD. The Thai translated scales Multidimensional Health Locus of Control Scales (MHLC), the SBI (Religious Beliefs/Practices), the Community Attitudes towards the Mentally Ill scale, the ADHD Stigma questionnaire (ASQ) (attitudes towards ADHD), Choi’s Analysis-Holism Scale, the ADHD Beliefs Scale-revised (perceptions of ADHD) were used for testing the model. The factor structure was examined via confirmatory factor analysis and reliability and validity were established initially before testing the model. Further, SEM was utilized to test the relationships between the aforementioned cultural factors and attitudes and perceptions of ADHD (n = 323). The results indicated significant relationships between cultural factors and negative opinions of ADHD. The current research aimed to contribute to the understanding of unique aspects of ADHD in Thailand. Future research may explore methods to increase knowledge of ADHD and reduce negative attitudes/perceptions of ADHD.